Analysis of Fuzzy Thinking Processess in Students’ Mathematical Communication at SMP Negeri 2 Banyumas - Helmy Wahyu Widiarti; Kusno Kusno; Anton Jaelani (Proceedings Series on Social Sciences & Humanities, 2025)
Fuzzy thinking means the thinking process with confusion between understanding and not understanding. This research was conducted to find out the students' experiences of fuzzy thinking in mathematics communication in SMP Negeri 2 Banyumas. This was a descriptive qualitative research and the subjects were taken from the students of class 8 C using snowball technique and T.O.L (Think Out Loud) that fulfilled the criteria of fuzzy thinking either the correct one or the incorrect one. From the results, there were 2 students with correct fuzzy thinking and 4 students with incorrect fuzzy thinking. The data were collected using tests, interviews, and documentation then analyzed using Miles and Huberman model consisting of data reduction, data display, and conclusion. The results showed that: 1) the thinking process of the respondents with incorrect fuzzy thinking experienced a change. At first they were able to think correctly, but after the reflection, they were not able to explain correctly, so the answers did not reflect their understanding absolutely; 2)the thinking process of the respondents with correct fuzzy thinking experienced a change. At first they were not able to do the test correctly, but after the reflection, they were able to finish it correctly.